THE EFFECT OF DIGITALIZATION OF HR MANAGEMENT ON EMPLOYEE PRODUCTIVITY IN THE ERA OF TECHNOLOGY-BASED ECONOMY - Prasetyo Iswahyudi; Khoirunnisa Larasati; Miko Andi Wardana (Journal of Economic, Bussines and Accounting (COSTING), 2025)
The development of a technology-based economy encourages organizations to undertake digital transformation across various aspects, including human resource management (HR). This study aims to analyze the influence of digitalization of HR management on employee productivity in the era of a technology-based economy. The research method used is a qualitative approach within the library research type. Research data were obtained from various reputable scientific literature, especially from Scopus-indexed international journals published in the last five years. The results of the study show that the digitization of HR management through the implementation of HR Information Systems, e-recruitment, e-learning, HR analytics, and digital-based performance management systems has a positive impact on increasing employee productivity. Digitization of human resources can improve the efficiency of work processes, enhance decision-making quality, and encourage innovative work behavior and employee engagement. However, the effectiveness of human resource digitalization is greatly influenced by organizational readiness factors, employee digital competence, leadership support, and a work culture that is adaptive to technology. This study concludes that the digitalization of HR management is an essential strategy for increasing employee productivity, but its success requires careful implementation planning and sustainable HR capacity-building.